PP.22.24: EFFECTS OF HIGH-PERFORMANCE SOCCER TRAINING ON FUNCTIONAL HAEMODYNAMIC PARAMETERS AND ARTERIAL STIFFNESS IN CHILDHOOD AND ADOLESCENCE. (June 2015) - Lay, D.; Brinkmann, C.; Jacobs, T.; Predel, H.G.
Abstract : Objective: Incidence and prevalence of cardiovascular diseases are increasing steadily, even in young age-groups. It is well known, that regular moderate endurance exercise has positive and protective effects on the cardiovascular system, whereas very high volumes of endurance exercise may be harmful in middle-aged and older individuals. There is a lack of data concerning young individuals in general and in young elite soccer players especially. Therefore, in the present study, the effects of high-performance soccer-training on haemodynamic regulation as well as on parameters of arterial stiffness in children and adolescents were evaluated. Design and method: 201 healthy male children and adolescents (10–18 years), including 118 young elite soccer players (14 ± 2 years) from the 1.FC Cologne and 83 sedentary school students (14 ± 2 years), were examined. After recording height, weight, body mass index and percentage of body fat, we determined vascular parameters at resting state before and immediately after an intensive treadmill exercise using an oscillometric validated device, measuring pulse wave velocity, augmentation index, augmentation index@75, central systolic blood pressure and central pulse pressure. Results: Age and body mass index positively correlated with pulse wave velocity (PWV) (r = 0.464 und r = 0.328; p < 0.05) and inversely with the heart rate corrected augmentation index (AIx@75) (r = -0.418 und r = -0.234; p < 0.05). Elite soccer players showed a significant higher performance capacity, lower heart rate and AIx@75 (7.5 ± 9, 5% vs. 15.3 ± 9, 5%; p < 0.05) in the resting state than sedentary school students. After exercise, PWV only increased in the athletes (before: 4.77 ± 0.40 m/s, after: 4.89 m/s; p < 0.05). AIx@75 significantly increased in both, in the athletes (before: 7.5 ± 9, 5 % after: 20.8 ± 7, 8 %; p < 0, 05) as well as in the school students (before: 15, 3 ± 9, 5 % after: 28, 7 ± 9, 5 %; p < 0, 05). Conclusions: In young elite soccer players no negative effects on the central haemodynamic system as well as on the arterial distensibility were observed. Furthermore, resting heart rate was significantly lower and exercise performance capacity was significantly higher compared to the age-matched non-trained school students. In summary, high-performance sports resulted in the expected positive effects and was not associated with negative impacts on the functional vascular regulation in childhood and adolescence.